Role of tamsulosin a selective alpha 1a-1d blocker vs. combination therapy of tamsulosin and solifenacin M3 antagonist in DJ stent related morbidity: obstructive and irritative scores - Lad, Vipul; Gandhi, Drashti; Agarwal , Gaurav; Bochiya, Girish (International Surgery Journal, 2023)
Background: nowadays Urolithiasis is very common in general population. Due to the advent of newer lithotripsy techniques, endoscopic procedures are used in most of the cases and to promote stone clearance DJ stents are kept after all the endoscopic procedures. Methods: This is a prospective study conducted among indoor patients from January 2021 to May 2022 in 90 indoor patients of tertiary care hospital. Results: In our study go 90 patients, pre DJ insertion, IPSS score in group A was 10.22 and Group B was 9.64, Mean Quality of Life in Group A was 1.77 and group B was 1.37, Visual analogue scale in group A was 2.08 and group B was 2.24. On Day 1 Post DJ insertion, IPSS score in group A was 12.26 and Group B was 11.68, Mean Quality of Life in Group A was 1.44 and group B was 1.28, Visual analogue scale in group A was 2.55 and group B was 2.28. Conclusions: Use of combination of selective alpha 1a-1d blocker and M3 antagonist significantly reduces the DJ stent related morbidity after endoscopic treatment for urolithiasis.